1997
DOI: 10.1073/pnas.94.26.14701
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of the diphtheria toxin A chain by a tumor-specific chimeric transcription factor results in selective toxicity for alveolar rhabdomyosarcoma cells

Abstract: Alveolar rhabdomyosarcoma (ARMS) cells often harbor one of two unique chromosomal translocations, either t(2;13)(q35;q14) or t(1;13)(p36;q14). The chimeric proteins expressed from these rearrangements, PAX3-FKHR and PAX7-FKHR, respectively, are potent transcriptional activators. In an effort to exploit these unique cancer-specific molecules to achieve ARMS-specific expression of therapeutic genes, we have studied the expression of a minimal promoter linked to six copies of a PAX3 DNA binding site, prs-9. In tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…HT-1080 and SKLMS1 cells were authenticated in May 2015. The Rhabdo CCL-136 cell line was derived from an embryonal rhabdomyosarcoma lacking t(2;13) and does not express PAX3-FKHR (44). This cell line was purchased from ATCC with valid STR in November 2014.…”
Section: Methodsmentioning
confidence: 99%
“…HT-1080 and SKLMS1 cells were authenticated in May 2015. The Rhabdo CCL-136 cell line was derived from an embryonal rhabdomyosarcoma lacking t(2;13) and does not express PAX3-FKHR (44). This cell line was purchased from ATCC with valid STR in November 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Under the control of a cell type-or tumor-specific promoter, the DT-A gene has been tested in cancer therapy (15)(16)(17)(18)(19). This bacterial protein is highly toxic when introduced into the cytoplasm of eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…We provide the evidence showing that, with the assistance of the engineered gene expression cassette, baculoviruses containing a cDNA encoding the A-chain of diphtheria toxin (DT-A; refs. [15][16][17][18][19] preferentially killed glioma cells in vitro and effectively inhibited the growth of glioma cells in the rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…As described, strategies were developed to antagonize PAX3 ± FKHR expression with antisense oligonucleotides or to antagonize PAX3 ± FKHR function with an engineered PAX3 ± KRAB transcriptional repressor Bernasconi et al, 1996;Fredericks et al, 2000). Another therapeutic strategy involves transfer of a construct consisting of PAX binding sites that regulate expression of a toxinencoding gene (Massuda et al, 1997). Cell culture studies demonstrated that this construct is selectively toxic for cells expressing the PAX3 ± FKHR fusion.…”
Section: Molecular Diagnostic and Therapeutic Studies Of Arms Gene Fumentioning
confidence: 99%